Rasionalitas Ekonomi: Perspektif Pilihan Konsumsi Rumah Tangga Muslim - Khairul Hanif; Mahyarni Mahyarni; Kiki Hardiansyah Siregar (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2026)
Rationality is a mindset and action pattern based on human reason and logic in making choices, including in economic activities. This study aims to examine and analyze the fundamental differences between the concepts of rationality in conventional economics and rationality in Islamic economics. The method used in this study is library research with a qualitative-descriptive approach. Data collection techniques were conducted through documentation of various relevant literature sources, such as books, scientific journals, and other academic works. The results of the analysis indicate that rationality from an Islamic perspective is more holistic in nature because it emphasizes not only material aspects but also moral and spiritual dimensions, with the primary goal of achieving falah, namely, well-being in this world and the hereafter. Muslim household consumption patterns are not solely directed at fulfilling personal needs but also consider social obligations and spiritual values. Factors influencing Muslim household consumption choices include religion, economic conditions, socio-cultural factors, and level of knowledge. The implications of this research are expected to provide a conceptual understanding that Islamic economic rationality offers an alternative paradigm to conventional rationality in explaining Muslim household consumption behavior.